A Total systems study on Wur Company - Dela Fuente, Janella; Madriñan, Sarah; Omictin, Michael Philip; Santos, Gari Lenard (Diliman, Quezon City College of Engineering, 2003)
The group conducted a Total Systems Study on WUR Company. WUR is a subcontractor for a large, multinational manufacturer of beauty products. The methodology of the study involved Phase 1 ? Data Gathering; Phase 2 - Documentation and Verification; and Phase 3 ? Problem Identification and Prioritization. The corporate values were evaluated into three main areas: Quality, Productivity, and Safety. System analysis was divided into two: short term and long term. For the short-term system analysis, three main problems addressed: lack of personnel at the client receiving area, excessive material handling, and client's order already met. Recommendations were made on these problems. For the long-term system analysis, Strengths-Weaknesses-Opportunities-Threats Analysis or SWOT and Performance Measure were conducted. Two future alternatives for the company were also formulated I line with the threat of the client company deciding to transact only with a single subcontractor. One is that the client will retain the company as its subcontractor and the other is the opposite, the exemption of the company from the list of suppliers. Each scenario requires massive changes for the company and alternatives were presented to help clarify which options to choose based in the decision of the client.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: WUR Company; Product management; Cosmetics industry; System design